2010
DOI: 10.1303/aez.2010.569
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal effects of nitenpyram on life-table parameters and wing formation of Nilaparvata lugens (Stål) (Homoptera: Delphacidae)

Abstract: The Nilaparvata lugens (Stål) is a major rice pest in Asia. Nitenpyram is a novel neonicotinoid insecticide developed by Takeda Chemical Industry Co., Ltd. The effects of sublethal concentration (LC 30 ) of this insecticide on life-table parameters and wing formation of N. lugens were studied in the laboratory. The results showed that nitenpyram could reduce the fecundity of N. lugens to a great extent and demonstrated further activity against this pest in addition to direct toxicity. The fecundity (eggs per f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 31 publications
(27 reference statements)
1
7
0
Order By: Relevance
“…Increased neonicotinoid-induced mortality also coincided with metamorphosis timing in A. mellifera 11 . These observations are further supported by similar effects reported in other insect taxa 12,13 . Complete insect metamorphosis includes the formation of the intermediate nonfeeding pupal (chrysalis) stage, which allows the formation of adult structures from pupal tissues or from the imaginal discs that have been present since embryogenesis 14 .…”
supporting
confidence: 89%
“…Increased neonicotinoid-induced mortality also coincided with metamorphosis timing in A. mellifera 11 . These observations are further supported by similar effects reported in other insect taxa 12,13 . Complete insect metamorphosis includes the formation of the intermediate nonfeeding pupal (chrysalis) stage, which allows the formation of adult structures from pupal tissues or from the imaginal discs that have been present since embryogenesis 14 .…”
supporting
confidence: 89%
“…The effect of SRBSDV on S. furcifera life table parameters and wing formation were determined using their life tables constructed according to the method described by Zhang et al (2010b). One hundred neonates were collected randomly from each cohort as founders of the experimental population and reared on the SRBSDV-infected or noninfected rice plants at tillering stage under the conditions described above.…”
Section: Methodsmentioning
confidence: 99%
“…It is known that sublethal concentrations of insecticides can impair fundamental behavioral and physiological traits of the target insects such as activity, appetite, foraging behavior, and fecundity (Wang et al 2008a;Qu et al 2014). Sublethal concentrations of insecticides leading to pest outbreaks in the field have been reported in many pests (Reissig et al 1982;Tripathi & Sachan 1990;Zhang et al 2010). For example, Bartlett (1968) reported that a sublethal level of organochlorine and organophosphorus insecticides could cause aphid resurgence.…”
Section: Introductionmentioning
confidence: 99%